Company performance analysis and tax aggressiveness - Taufik, Ruhiyat; Hasanah, Hani; Lestari, Sri; Dharmayanti, Nela; Sriharyanti, Resty (International research journal of management, IT and social sciences, 2022)
This study aims to determine the effect of return on assets, firm size, leverage and intensity of fixed assets, both partially and simultaneously on tax aggressiveness in LQ 45 companies listed on the Indonesia Stock Exchange in 2015-2018. The analytical method used is panel data regression analysis. The sample selection technique used was purposive sampling and obtained 35 LQ 45 companies with a research period of four years, 2015-2018, so that 140 units of observation were obtained. The results showed that the variable return on assets and the variable intensity of fixed assets partially had a significant effect on tax aggressiveness. Meanwhile, company size and leverage partially have no effect on tax aggressiveness.